National launch: PlaSA Colombia, Keeping track of food in the country - Betancourt, Daniela Salas; Rankin, Sara; Castillo, Johana M. (CGIAR System Organization, 2023)
The national launch of the Food Systems Platform – PlaSA Colombia, developed within the framework of the National Policies and Strategies initiative, took place on April 27th at the Universidad de Los Andes in Bogota. This initiative contributes to the construction of more solid policies and strategies, with greater coherence and capacity, to help meet current policy demands and future development needs. The event had 60 attendees in person and 593 visits to the live broadcast on YouTube, an audience that, with their questions energized the panel and allowed addressing the challenges currently facing the food system from different perspectives.